Impact of a Task-Grabbing System for surgical technicians on operating room efficiency - Xiuwen Chen; Jiqun He; Luofang Peng; Li Lin; Pengfei Cheng; Yao Xiao; Shiqing Liu (Scientific Reports, 2024)
Abstract The purpose of this study was to evaluate the effect of the Task-Grabbing System on operating room efficiency. Based on the competition-driven concept of the ‘Uber’ app, an Task-Grabbing System was designed for task allocation and quality assessment. We implemented the Task-Grabbing System in our hospital operating room and compared the differences in consecutive operation preparation time, turnover time, and task completion time performed by surgical technicians for tasks such as patient pick-up, operating room cleaning, medical equipment recovery, three-piece set delivery, as well as blood gas analysis and intraoperative specimen submission before (October 2019) and after (December 2019) the implementation of the Task-Grabbing System. After the implementation of the Task-Grabbing System, the consecutive operation preparation time was reduced from the average of 43.56–38.55 min (P < 0.05), and the turnover time was decreased from the average of 14.25–12.61 min (P < 0.05). And the respective time consuming of surgical technicians for patients picking up, operating room cleaning, medical facilities recovering, the three-piece set delivering, blood gas analysis sending and intraoperative specimen submitting was significantly shortened (P < 0.05). The Task-Grabbing System could improve the operating room efficiency and effectively mobilize the enthusiasm and initiative of the surgical technicians.